Representações sociais sobre o cuidado construídas por idosas - Araújo, Verbena Santos (2015)
The aim of this study has been to explore Social Representations about care built by elderly women towards human aging. it is an exploring, descriptive, and transversal study with qualitative approach, guided through the Social Representation Theory, remarking the dimensions (information or knowledge, placing or attitude, and image or field of representation). the empirical material was originated from semi-structured interviews applied to 40 elderly women who participated in social groups, divided equitably into elderly graduated in the course of Education for Healthy Aging at the University Open to Maturity, linked to the Sate University of Paraiba - UEPB (Group 1), and elderly women taking part in the Elderly Familiarity Center, in the county of Campina Grande/PB (Group 2). the collect of data was made in the months from October to December, 2014, and strictly followed the assumptions of Resolution 466/2012 of the National Health Council, about researches involving human beings, having been approved by the Ethic Committee on Institutional Research, through note nº 612/10. The data were collected from semi-structured interviews turned to Social Representation about the study object, and were processed by the software of textual analysis IRAMUTEQ. the Descendant Hierarchical Classification (DHC) kept 84.45% from the extracts, meaning that the utilization was of 603 from the 714 present in the corpus, organized in five response classes of the elderly associated to care towards human aging, which were promptly nominated by the researcher and analyzed afterwards: Class 1: the care while aging; Class 2: Possibilities to learn along the aging; Class 3: affective relations of the care along the aging; Class 4: freedom to locomotion in aging, discovery of autonomy; Class 5: care as general attitude, set of practice along aging. The Social Representations of care highlighted in the five classes meant singularities in old age which led to a self care, thus taking a behavior to "take care of the care". In the classes 1 and 5 the care was worked from more factual aspects, folowing prevention actions and attitudes, noting physiological, preventive, and curative content, relating to the aging process itself, helping in the conservation of autonomy of the elderly and physical, psychological, and social welfare, featuring the dimension placing or attitude of social representations, whereas the other classes pointed to representations turned to more subjective aspects of the care, as observed in class 2, featuring dimension knowledge or information about the studied phenomenon, showing that the contribution of the social environment around the elderly person is essential for the practice of the care itself during this time of the life, in class 3 which brought affective relations surrounding social relations of the elderly, and class 4 which mentioned the freedom for locomotion as possibility of socialization, these classes featuring image dimension or representation fields. The groups shared Social Representations about the care leading to the same reality, the one which says that the care itself is essential for keeping welfare and satisfaction to enter and live the so called third age fully, that this care must be the way for life changing as well as adopting healthy practice, while there are important approaches between the two groups studied here, not having divergence about behaviors or practices set. The analysis allowed us to know the subjective dimensions about the care towards human aging, a behavior which is socially typical and shows meaningful changes in the lives of elderly women, mainly about new experiences and opportunities highlighted in the Social Representations learned.